2020
DOI: 10.2147/cmar.s234897
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-27a-3p Regulated the Aggressive Phenotypes of Cervical Cancer by Targeting FBXW7</p>

Abstract: Background: Abnormally expressed microRNAs (miRNAs) contribute greatly to the initiation and development of human cancers, including cervical cancer, by regulating the target mRNAs. MiR-27a-3p was up-regulated and acted as an oncogene in multiple cancers. However, the function of miR-27a-3p in cervical cancer has not been fully understood. Methods: The expression of miR-27a-3p in cervical cancer tissues and cell lines was detected by RT-pPCR. MTT assay, colony formation assay and flow cytometry analysis were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In the present research, the mir-27a-3p expression in degenerative NP tissue, and cell was obviously lower in comparison with the control group. A lot of reports showed that mir-27a-3p was higher expressed in a series of cancers and impede cell apoptosis [14][15][16]. Mir-27a-3p in glioma tissues was obviously expressed lower in comparison with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In the present research, the mir-27a-3p expression in degenerative NP tissue, and cell was obviously lower in comparison with the control group. A lot of reports showed that mir-27a-3p was higher expressed in a series of cancers and impede cell apoptosis [14][15][16]. Mir-27a-3p in glioma tissues was obviously expressed lower in comparison with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…We also described herein that the miRN-27-a-3p showed a significant differential expression in tears from the POAG patients and the OHT participants. This miRNA has been implicated in cell proliferation and apoptosis in different types of cancer [ 43 , 44 ]. Overexpression of this miRNA promotes proliferation and inhibits apoptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from involvement in cancer, downregulation of FBXW7 by miR-322 demonstrates a possible curing method to protect myocardium from ischemia/reperfusion injury. Collectively, there are still other miRNAs, such as miR129 (61), miR-92a-3p (62), miR182 (63), miR-27a-3p (64,65), miR-212/132 (66), miR-223-3p (67), miR-103a-3p (68), miR-25 (69), miR−25−3p (70), miR-144 (71), miR-101 (72), miR-188-5p (73), and miR-500a-3p (74), functioning discrepantly to mediate different cell phenotypes but via the identical mechanism of targeting FBXW7.…”
Section: Microrna Regulation Of Fbxw7mentioning
confidence: 99%